AI-assisted dietary assessment and personalised “nudges” in urban youth: Feasibility and effectiveness of a mobile phone-based intervention to improve diets in Ghana - Gelli, Aulo; Folson, Gloria; Nwabuiku, Odiche; Bannerman, Boateng; Ador, Gabriel; Atadze, Vicentia; Asante, Millicent; McCloskey, Peter; Nguyen, Phuong Hong; Hughes, David (International Food Policy Research Institute, 2023)
Diet-related risks cause 20% of global deaths (~11 million) per year (Afshin et al., 2019). Increased urbanization in low- and middle-income countries accompanied by a nutrition transition, involving increased consumption of unhealthy, processed foods and reductions in physical activity, has exacerbated diet-related risks, leading to increases in rates of overweight and obesity (Popkin et al., 2020). Diets in urban settings are also affected by the reduced time for food preparation, convenience and affordability of unhealthy foods.